Super bull Mkombozi a symbol of high potential growth for Tanzania dairy - International Livestock Research Institute (International Livestock Research Institute, 2019)
Mbeya, Tanzania. Meet Lukas Mwambona and his bull, Mkombozi. Through genetics and data gathering, Mkombozi has been identified as one the country's top productive and environmentally resilient bulls under the African Dairy Genetic Gains (ADGG) program of ILRI and the CGIAR Research Program on Livestock. ADGG is working to unlock the potential of Tanzania's dairy sector by identifying and delivering more productive and profitable dairy cows.